Ideology in Narendra Modi’s Speech: A Critical Discourse Analysis - Tanjung, Apida Fauziah; Marisha Putri, Dian (Talenta Publisher, 2024)
This study investigates the application of Critical Discourse Analysis to Narendra Modi's speech Maan Ki Baat. In this research, the focus is on the text structure and the ideology represented in the speech. The theory used is Van Dijk’s text structure model which concentrates on the three elements of text structures; macrostructures, superstructures, and microstructures. The research adopts qualitative research using critical discourse analysis to analyze the data. The data were analyzed through Van Dijk’s text structure model. The data collected from https://www.youtube.com/watch? v=oEB5RnaDZmE. This study has revealed that first the macrostructure of three speeches is about Prime Minister Narendra Modi asked Indians to stay more vigilant than ever against the threat of COVID-19. Second, the superstructure of the three speeches gives information about the condition of Indians and poor people against the effect of covid-19 and his recommendation to people in following the protocol during the pandemic period. Third, the microstructure of the three speeches depicts that Modi intended to provide a positive image in his speech therefore, the positive word is used in the speech. Thus, the ideology represented in the text is socialism.